CFD Simulations Of Enhancement Of Jet Mixing By Lateral Synthetic Jet Pair - Hong, Mun Hoh (2020)
The use of synthetic jet in enhancing mixing ensures the success of many applications, including biomedical devices and chemical processing. Previous studies have found that modifications of the orifice edges and orifice width can alter the jet flow characteristics particularly in regard to flow mixing behaviours. It is expected that a change in these parameters could improve the mixing effectiveness of jet mixing technique. Therefore, the main goal of this research was to investigate the mixing characteristics of synthetic jet under the influence of various orifice edge configurations at different orifice width. First, a CFD model was developed for the evaluation of synthetic-jet-enhanced mixing performance in a mixing channel. The numerical modelling utilized a viscous laminar model to simulate the unsteady incompressible flow 3D model under a net flow Reynolds number of 83. Validation and verifications were conducted to examine the quality of the results. The mixing mechanisms and influence of three different orifice edges configurations (sharp, rounded, and chamfered) at different orifice widths (1.6, 2.4 and 4 mm) on the mixing degree between two fluid streams were then identified and discussed. The findings indicated that there is an optimal ratio of orifice width to the width of the mixing channel (d/h = 0.3), which will give the best mixing degree with a value of 0.6584 for a given width of the mixing channel with sharp-edged orifice. The findings also revealed that the rounded orifice showed the best mixing degree with a value of 0.6201 at lower d/h whereas the sharp-edged orifice showed the best mixing degree with a value of 0.6584 at higher d/h. This research work will serve as a guideline for selecting a suitable orifice width and orifice edge configuration to enhance the mixing performance of a synthetic-jet-assisted fluid mixer.